2008
DOI: 10.1007/s11745-008-3202-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Tumor Effect of Orally Administered Spinach Glycolipid Fraction on Implanted Cancer Cells, Colon‐26, in Mice

Abstract: We succeeded in purifying a major glycolipid fraction from a green vegetable, spinach. This fraction consists mainly of three glycolipids: monogalactosyl diacylglycerol (MGDG), digalactosyl diacylglycerol (DGDG), and sulfoquinovosyl diacylglycerol (SQDG). In a previous study, we found that the glycolipid fraction inhibited DNA polymerase activity, cancer cell growth and tumor growth with subcutaneous injection. We aimed to clarify oral administration of the glycolipid fraction, suppressing colon adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 32 publications
(46 reference statements)
1
26
0
Order By: Relevance
“…MGDG and DGDG have potential anticancer 9 functions due to DNA polymerase inhibition, suppression of cancer cell proliferation, antiangiogenesis and anti-tumor promotion properties [40][41][42][43]. Indeed, glycolipid fraction of spinach has shown anti-tumor activity with oral administration in colon tumor in mice.…”
Section: Galactolipids Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MGDG and DGDG have potential anticancer 9 functions due to DNA polymerase inhibition, suppression of cancer cell proliferation, antiangiogenesis and anti-tumor promotion properties [40][41][42][43]. Indeed, glycolipid fraction of spinach has shown anti-tumor activity with oral administration in colon tumor in mice.…”
Section: Galactolipids Applicationsmentioning
confidence: 99%
“…Moreover, it has been observed that the hydrolized form of biological glycolipids, in particular hydrolized MGDG, has more anti-tumor activity than the non-hydrolized form [41]. DGDG and, in particular, MGDG have an important anti-inflamatory activity, which is reduced when increasing the saturation index [40].…”
Section: Galactolipids Applicationsmentioning
confidence: 99%
“…Previous voltammetric results of phospholipid layers containing quinone derivatives [13,[15][16][17][18][19] and the fact that UQ size and shape are close to those of PQ, make UQ a suitable candidate for substituting PQ, which isolation process has a huge cost, in studies of artificial photosynthesis. 3 Several studies have been performed on galactolipids due to their relevance in photosynthesis and other natural processes like cell growth modulator [20], anti-inflammatory [21,22] and anti-cancer agent [23][24][25][26]. One of the most relevant model membrane information is the galactolipid phase behaviour, especially its liquid-crystalline packing properties which has been widely investigated [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, algae represent valuable sources of a wide spectrum of complex lipids, and their components have promising potential applications especially in the food, cosmetic, and pharmaceutical industries (Hossain et al, 2005). The various biological actions of SLs include: inhibitory effects on DNA polymerase and viral reverse transcriptase, antitumor, anti-inflammatory, and inhibition and promotion of cell growth Liptak et al, 2004;Maeda et al, 2008;Naumann, 2009)…”
Section: Introductionmentioning
confidence: 99%